2011
DOI: 10.1002/pi.3101
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted β‐cyclodextrin polymers using naringin as template

Abstract: The objective of this study was to identify a kind of molecular imprinting polymer (MIP) which was suitable for recognizing naringin (NG) in aqueous medium. Based on two crosslinkers (hexamethylene diisocyanate and epichlorohydrin) and two polymerization methods (solution polymerization and emulsion polymerization), four non‐covalent naringin‐β‐cyclodextrine (NG‐β‐CD) imprinted polymers were prepared by using β‐CD as a functional monomer and NG as a template molecule. The binding property and selectivity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Ma et al. studied two polymerization methods (solution polymerization and emulsion polymerization) and two crosslinkers (hexamethylene diisocyanate and epichlorohydrin) for recognizing naringin, a kind of flavonoid which is widely distributed in plants, especially in the skins and seeds of fruits and vegetables, in aqueous medium . The authors synthesized four noncovalent naringin‐imprinted polymers by using β‐CD as a functional monomer in DMSO solvent by hydrogen bond interaction during MIP preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. studied two polymerization methods (solution polymerization and emulsion polymerization) and two crosslinkers (hexamethylene diisocyanate and epichlorohydrin) for recognizing naringin, a kind of flavonoid which is widely distributed in plants, especially in the skins and seeds of fruits and vegetables, in aqueous medium . The authors synthesized four noncovalent naringin‐imprinted polymers by using β‐CD as a functional monomer in DMSO solvent by hydrogen bond interaction during MIP preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In additional, compared with the imprinting factor α of HD (α = 1.11 ± 0.16), the imprinting factor α of NG is 1.74±0.20, which suggested that imprinted cavities played an important role in recognition. As shown in Figure , the imprinting factor of NG (4#) is slightly lower than that for the imprinted β‐cyclodextrin nanofiber with in‐situ generated silica as pore‐forming agent (5#), comparable to the values for the imprinted 5‐P (AN‐co‐IA) membrane (3#) and the imprinted β‐cyclodextrin nanofiber (2#), but better than the one for the imprinted β‐cyclodextrin polymer (1#) …”
Section: Resultsmentioning
confidence: 70%
“…As the recognition of flavonoids in aqueous media is a bit challenging due to poor affinities, there is growing interest in producing MIPs . The recognition of NG was performed in aqueous medium using β‐cyclodextrin (β‐CD) as functional monomer . But it was difficult to find an excellent crosslinker.…”
Section: Introductionmentioning
confidence: 99%
“…β-CDs have been also used as functional monomers to interact with naringin molecules via hydrogen bonding in molecularly imprinted polymers synthesised using the fl avonoid as target molecule. In a recent study [50], Ma et al, developed an imprinted β-CD polymer capable to bound 50.13 μmol/g polymer of naringin.…”
Section: Cyclodextrins As Molecular Recognition Elementsmentioning
confidence: 99%